Awareness : facilitating the therapeutic dance along the path of growth and change ; evaluating the psychometric properties of a therapist schema questionnaire : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Phin, Rebekah Jenny (Massey University, 2013)
The importance of the therapeutic relationship and the therapist’s contribution to the interpersonal processes, have been increasingly recognized as important factors in Cognitive Behavioural Therapy change and outcome. More specifically, the therapists’ understanding and awareness of their own beliefs, assumptions and schema, and the potential effect that they can have on therapy, has been increasingly emphasized. Leahy’s (2001) Therapist Schema Questionnaire (TSQ) is a potentially useful screening measure designed to identify Therapist Schema. No research has evaluated the psychometric properties of the TSQ. This study investigated the underlying factor structure and reliability of the TSQ in a therapist sample (N = 269). An exploratory factor analysis suggested a 7 factor structure and a 37 item scale that included 4 of the original 15 schema factors, as well as 3 additional factors, each containing a theoretically meaningful combination of original schema factors. The 3 most commonly identified Therapist Schemas revealed in the study were ‘self-sacrifice’, ‘demanding standards’, and ‘sensitive/rejection’. The identified factors and the 37 item scale were found to have adequate to good internal consistency. Implications of these findings are discussed and recommendations are made for further research.
Keywords: Cognitive behavioural therapy; Cognitive Behaviour Therapy; Cognitive behaviour therapists; Therapeutic relationship; Schema; Self-awareness; Self-reflection